Usagi yojimbo (1996), volume 19 ebook Fathers and sons. - Sakai, Stan (Usagi Yojimbo (1996), 2016)
Master storyteller Stan Sakai opens this brand-new collection with a deadly ambush on the fugitive Lone Goat Assassin and his child, Gorogoro. Lone Goat is victorious, but wounded-and his son is too young to help. Unable to seek proper medical attention, Lone Goat collapses in an abandoned house. What he needs is a knowledgeable ronin, and soon! Elsewhere, Usagi is in a desperate search for his young companion, Jotaro, who has eluded murderous kidnappers. His is a panic that only rises out of fatherly love, though he has kept the secret of Jotaro's parentage from the boy throughout their travels together. If they are able to continue on to Kitanoji Temple, will the rabbit samurai confess before they part ways? Featuring appearances by readers' favorite characters-including the deadly Neko Ninja. Collecting issues #69-#75 of the ongoing series.